The Effectiveness of Task-Based Language Teaching in Enhancing High School Students’ Communicative Competence - Aliyah Riyanti Nasir (LIER: Language Inquiry & Exploration Review, 2025)
Purpose: This study aims to examine the effectiveness of Task-Based Language Teaching (TBLT) in improving the communicative competence of high school students learning English, addressing the gap between grammar-based instruction and the development of authentic communication skills. Subjects and Methods: A quasi-experimental quantitative design was employed, involving an experimental group taught using TBLT and a control group taught through conventional grammar-based methods. Communicative competence was measured across four dimensions grammatical, sociolinguistic, discourse, and strategic using a standardized rubric applied in pre-test and post-test evaluations. Data analysis was conducted through paired-sample and independent-sample t-tests, with effect sizes determined using Cohen’s d. Results: The findings revealed that students in the experimental group achieved significantly greater gains in all areas of communicative competence compared to the control group, with large effect sizes confirming the strong impact of TBLT. Beyond measurable improvements in language performance, TBLT also fostered higher engagement, peer collaboration, and strategic language use, bridging classroom instruction with real-world communicative practices. Conclusions: The study provides robust empirical evidence supporting the integration of TBLT into high school curricula. It underscores the need for systemic support in teacher training, effective task design, and performance-based assessments to ensure sustainable and impactful implementation.